Ethical Perceptions of Tax Avoidance and Spiritual Balance Dimensions - I Gusti Ayu Purnamawati; Evan Lau Poh Hock; Gede Adi Yuniarta (Institute of Research and Community Outreach - Petra Christian University, 2023)
This research is about tax avoidance viewed from the perspective of gender and business scale in analyzing ethical perceptions. This study was conducted using primary data by collecting questionnaires distributed to small and medium-sized industrial entrepreneurs in the province of Bali. The samples used were 52 female entrepreneurs and 48 male entrepreneurs. A comparison of ethical perceptions of tax avoidance was tested using Wilcoxon. The research shows no significant difference between the ethical perceptions of small and medium entrepreneurs on tax avoidance and the moral perceptions of male and female entrepreneurs. The correct tax policy must convince taxpayers to fulfil their obligations, primarily through a spiritual dimension that can strengthen taxpayers' confidence not to commit moral hazard. This study adopts the concept of Rwa Bhineda because today's world will lead to the black-and-white era referred to as Rwa Bhineda.